Verteporfin Photodynamic Therapy Combined with Intravitreal Ranibizumab for Polypoidal Choroidal Vasculopathy Controversy Concerning Long-Term Followup - Maribel Fernández; María Gil; Francisco Gomez-Ulla; Pablo Charlón (Case Reports in Medicine)
Purpose. To show the long-term results of intravitreal ranibizumab combined with photodynamic therapy (PDT) for the treatment of polypoidal choroidal vasculopathy (PCV). Methods. We analyzed the progress of two patients for 36 and 58 months, respectively. We only used PDT for the treatment in the area of the active PCV or “hot spot” evident on the indocyanine green angiography (ICGA). The spot size was chosen so as to cover only the active neovascular lesion. We combined intravitreal ranibizumab with PDT when PCV remained active without visible polyps in ICGA or without a response to PDT. Conclusion. Administration, as required, of verteporfin photodynamic therapy combined with intravitreal ranibizumab is an effective treatment for symptomatic polypoidal choroidal vasculopathy. These data need to be confirmed in large, prospective, and controlled clinical trials which are randomized and carried out over a long period.